Synthesis of Novel Derivatives of Carbazole-Thiophene, Their Electronic Properties, and Computational Studies - Damit, E.F.; Nordin, N.; Ariffin, Azhar; Sulaiman, K. (Hindawi Publishing Corporation, 2016)
A series of carbazole-thiophene dimers, P1–P9, were synthesized using Suzuki-Miyaura and Ullmann coupling reactions. In P1–P9, carbazole-thiophenes were linked at the N-9 position for different core groups via biphenyl, dimethylbiphenyl, and phenyl. Electronic properties were evaluated by UV-Vis, cyclic voltammogram, and theoretical calculations. Particularly, the effects of conjugation connectivity on photophysical and electrochemical properties, as well as the correlation between carbazole-thiophene and the core, were studied. Carbazole connecting with thiophenes at the 3,6-positions and the phenyl group as a core group leads to increased stabilization of HOMO and LUMO energy levels where the bandgap () is significantly reduced.